2014
DOI: 10.1016/j.febslet.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction regulation by calmodulin

Abstract: Intracellular Ca2+ activated calmodulin (CaM) inhibits gap junction channels in the low nM to high μM range of [Ca2+]i. This regulation plays an essential role in numerous cellular processes that include hearing, lens transparency, and synchronized contractions of the heart. Previous studies have indicated that gap junction mediated cell-to-cell communication was inhibited by CaM antagonists. More recent evidence indicates a direct role of CaM in regulating several members of the connexin family. Since the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 92 publications
3
63
0
Order By: Relevance
“…Indeed, our ITC data also shows that this interaction is primarily driven by an enthalpic change, meaning an electrostatic change. Previous papers suggest the electrostatic interactions between Cx44 (ovine ortholog of Cx46) and CaM (16,27). The ITC experimental data demonstrated that the stoichiometry between Cx46MT and CaM is one to one, which is consistent with predicated interaction between Cx44 and CaM.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Indeed, our ITC data also shows that this interaction is primarily driven by an enthalpic change, meaning an electrostatic change. Previous papers suggest the electrostatic interactions between Cx44 (ovine ortholog of Cx46) and CaM (16,27). The ITC experimental data demonstrated that the stoichiometry between Cx46MT and CaM is one to one, which is consistent with predicated interaction between Cx44 and CaM.…”
Section: Discussionsupporting
confidence: 68%
“…It has been shown that α-helicity of the IL domain of connexins contributes to the binding of CaM and helps stabilize protein conformation (27). Surprisingly, α-helical content was greatly reduced in the IL domain containing G143R mutation despite tighter binding to CaM.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Cx50 exhibited a significant decrease in hydrodynamic radius of 5.3 Å that is consistent with a collapsed complex formation [49]. This result further suggested that binding of Cx45p 164–186 to CaM involves an extended conformation that is different from α-connexin Cx50 with an embraced compact form [34,49]. …”
Section: Resultsmentioning
confidence: 89%
“…Various past studies have proposed that CaM may play an active role in the regulation of gap junctions comprised of all three connexin subfamilies [3437]. Evidence of CaM’s role in regulation of Cx45 was first reported by Peracchia et al by monitoring the sensitivity of Cx45 channels to CO 2 and inhibiting CaM expression in oocytes [38].…”
Section: Introductionmentioning
confidence: 99%
“…2A and B). In addition, the CaM binding sites of several intracellular domains of connexins blockade gapjunction channels (Zou et al, 2014b). Overall, the interaction between GJIC and calcium pathways has an important role in Cd-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%